2004
DOI: 10.1023/b:mcbi.0000038228.85494.3b
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial signaling pathways: A receiver/integrator organelle

Abstract: Research over the last decade has extended the prevailing view of cell mitochondrial function well beyond its critical bioenergetic role in supplying ATP. Recently, it has been recognized that the mitochondria play a critical role in cell regulatory and signaling events, in the responses of cells to a multiplicity of physiological and genetic stresses, inter-organelle communication, cell proliferation and cell death. Nevertheless, a broad-based review on mitochondrial signaling is not presently available. To b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
125
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 135 publications
2
125
0
1
Order By: Relevance
“…It has been shown that mitochondrial kinases and phosphatases are under the control of intraluminal Ca 2+ [18], an effector that is already known to adjust the activity of many metabolic and anti-oxidative enzymes within mitochondria [12,17]. This observation indicates that mitochondrial Ca 2+ accumulation is a crucial phenomenon for the immediate regulation of mitochondrial protein phosphorylation.…”
Section: Reversible Protein Phosphorylation By Constitutive Kinases Amentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that mitochondrial kinases and phosphatases are under the control of intraluminal Ca 2+ [18], an effector that is already known to adjust the activity of many metabolic and anti-oxidative enzymes within mitochondria [12,17]. This observation indicates that mitochondrial Ca 2+ accumulation is a crucial phenomenon for the immediate regulation of mitochondrial protein phosphorylation.…”
Section: Reversible Protein Phosphorylation By Constitutive Kinases Amentioning
confidence: 99%
“…Mitochondria then integrate these inputs, adapting their activity and functions to, ultimately, tune cellular responsiveness with respect to the current demand of the cell [12] (Figure 1). In spite of the important tasks of the mitochondrion and in contrast to its functions in energy metabolism, its contribution to signal transduction has not been thoroughly investigated, and the [24,25].…”
Section: Mitochondrial Relay Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria play central roles in cellular energy metabolism, as well as in the regulation of cell cycle progression, apoptosis, and aging processes (1,2). Despite their importance, signaling into, from, and within mitochondria is still not well understood.…”
mentioning
confidence: 99%
“…Mitochondria are primarily energy-generating systems, the final step of which is oxidative phosphorylation coupled with an electron transport chain, supplying ATP. Having a pivotal role in the bioenergetic process, mitochondria are also critical to signaling events, receiving and integrating dynamically a wide range of signaling molecules from calcium ion to protein kinases, receptors and transcription factors (Goldenthal and Marin-Garcia, 2004). Although numerous studies have focused on the integral role of mitochondrial signaling cascades in apoptotic progression, mitochondrial signaling is prominently involved in proliferative pathways, nutrient sensing, inter-organellar communication and stress responses of cells (Goldenthal and Marin-Garcia, 2004).…”
Section: Discussionmentioning
confidence: 99%